A Re-evaluation of the Eucnemidae larval characters (Coleoptera) - Muona, Jyrki; Teräväinen, Marianna (Papéis Avulsos de Zoologia, 2020)
The larval characters of Eucnemidae are re-evaluated. Tribe Schizophilini Muona, 1993 is considered to merit subfamily rank as Schizophilinae Muona new status. Larval characters congruent with previously used adult morphological characters support the earlier published sister-group hypotheses for lignicolous eucnemids with one exception, Pseudomeninae, which is here split resulting in the following evolutionary hypothesis: (Pseudomeninae (Schizophilinae (Paleoxeninae (Melasinae, Eucneminae, Macraulcinae)))). The position of three remaining clades, Anischiinae, Perothopinae and Phyllocerinae remain ambiguous.